1996
DOI: 10.1530/jrf.0.1080081
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the scrotum and testes to scrotal and testicular thermoregulation in bulls and rams

Abstract: A novel model was used to determine the role of the scrotum and testes in scrotal/testicular thermoregulation in bulls and rams. Eleven yearling bulls and 12 yearling rams were used at an ambient temperature of 15 degrees C. The distal lateral aspects and entire ventral part of the scrotum were incised under caudal epidural analgesia (xylazine, 0.07 mg ml-1). Both testes were withdrawn from the scrotum, the vaginal tunic was removed and one testis was replaced in the scrotum. Surface and internal temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 9 publications
2
15
1
4
Order By: Relevance
“…The accuracy of thermography in our series was 100%, but the sensitivity was much lower than in the report of Goblyos et al [21]. This may be due to the fact that thermography was performed nonselectively in our series: the locations of all undescended testes varied from internal inguinal ring to high scrotum, and the lower located testes have lower detecting rates because of the lesser temperature differences compared with the surrounding tissues [20, 23, 24]. In older patients, the role of thermography is also questionable in hairy areas of the body.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The accuracy of thermography in our series was 100%, but the sensitivity was much lower than in the report of Goblyos et al [21]. This may be due to the fact that thermography was performed nonselectively in our series: the locations of all undescended testes varied from internal inguinal ring to high scrotum, and the lower located testes have lower detecting rates because of the lesser temperature differences compared with the surrounding tissues [20, 23, 24]. In older patients, the role of thermography is also questionable in hairy areas of the body.…”
Section: Discussioncontrasting
confidence: 58%
“…As for the utilization of thermography to localize undescended testes, there are only few reports and no comparative data between physical palpation or other objective diagnostic methods [21, 22]. It was reported that although the scrotal surface temperature is lower than the intratesticular temperature, the temperature of testis is uniform and lower than body core temperature [20, 23, 24]. This natural phenomenon is essential for the sperm production, and may be the reason why the undescended testes have a lower temperature than adjacent tissue, especially when they were intra-abdominal.…”
Section: Discussionmentioning
confidence: 99%
“…The supratesticular artery is closely associated with veins of the pampiniform plexus, which is often referred to as the “vascular cone” [26, 27]. In bulls, the cone-shaped pampiniform plexus encases the spiral-shaped supratesticular artery to cool blood before entering the testes [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Barth and Oko (1989) indicated a genetic predisposition for the development of specific sperm abnormalities in response to adverse conditions like elevated testicular temperature. The testicular temperature is kept within optimal limits by complex physiological mechanisms involving the scrotum, the testicular vascular cone and testes themselves (Waites and Moule 1961;Kastelic et al 1996Kastelic et al , 1997. Therefore, scrotal skin thickness could be involved in the thermoregulation of the testis and its variation can affect the semen quality.…”
Section: Discussionmentioning
confidence: 99%